Compreendendo as determinações sociais da saúde a partir da prática interdisciplinar na pediatria do HU/USP - Moura, Fernanda da Silva (2011)
This master's thesis aims to understand the process of health and disease as well as the social determinants that emerges during the hospitalization of children and adolescents admitted to the Pediatrics Ward of the University Hospital of the University of São Paulo. The study sought to clarify issues related to the subject's health as a result of his lifestyle or routine. The other purpose of the study was to identify the interdisciplinary team, whether to acknowledge the work of the Social Determinants of Health, or whether they remain within the concept of health with the absence of disease. The theoretical and historical materialism was used as a methodology to reflexive interview with the semi-structured. The field investigation led to the confirmation that practice is what distinguishes interdisciplinary team to work with is extremely complex demands. Family members interviewed demonstrated weakness in understanding the issues that go along with the sickness, but felt reassured by receiving attention from professionals. During this study the peculiarities of each group, professionals, and families were discussed. The reflections generated stronger bias in the work shared between the different areas, and multiply the total knowledge at the time of operation. In relation to the families there is a need for further understanding and familiarity of lifestyle. This is already somewhat happening, but the closer proximity to reality then the greater security the team will have in their behavior